Moraxella catarrhalis Macrolide-Resistant Isolates Are Highly Concentrated in Two MLST Clonal Complexes -CCN10 and CC363 - Liu, Ya-Li; Xiao, Meng; Cheng, Jing-Wei; Xu, He-Ping; Xu, Zhi-Peng; Ye, Sha; Zhang, Wen-Juan; Kudinha, Timothy; Kong, Fanrong; Xu, Ying-Chun (Frontiers in Microbiology, 2017)
To gain some insights into the molecular evolution of M. catarrhalis macrolide resistance, PCR and sequencing analysis of the 23S rRNA gene, copB typing and multilocus sequence typing (MLST) were performed on 181 M. catarrhalis isolates. The isolates were obtained from children (n =47) and adults (n=134) presenting with respiratory disease in the years 2010 - 2014. Macrolide resistance was highly age-related, and nucleotide position alterations at A2330T could be detected in all macrolide-resistant isolates. copB 0 and copB NT (non-typable) were only found in macrolide-susceptible isolates from adults. Furthermore, copB I/III was the main type in adult or macrolide-susceptible isolates, while copB II was the most common type in children or macrolide-resistant isolates. Twenty-two different MLST clusters (sharing 7 of the 8 identical loci) were detected and only four likely primary founders (ST224, ST363, STN08, STN10) which belong to clonal complex (CC) 224, CC363, CCN08, and CCN10, were detected respectively. Macrolide-resistant M. catarrhalis isolates were highly concentrated in two clonal complexes (CCN10 and CC363), which indicates some potential evolutionary advantage or co-evolution to some extent. However, further studies are needed to fully elucidate the evolution of CCN10 and CC363 in macrolide resistance.